Phonological development: acquisition of hausa secondary consonants by the hausa children / Sani Dauda Ibrahim - Ibrahim, Sani Dauda (Universiti Teknologi MARA, Kedah, 2019)
Phonological development refers to the stages that children pass before they can correctly use and understand the sound system of their language. Inspired by Stampe’s (1969) Natural Phonology Theory, this paper examines the acquisition of Hausa secondary consonants pronunciation by the Hausa children. The paper seeks to achieve the following objectives (a) to identify the phonological processes that are operating in the production of the Hausa secondary consonants by the Hausa 2-5 years children (b) to discover the units that are more affected if certain changes occur in the production of the Hausa secondary consonants (c) to explain whether a parental behavior influence the children’s production of the Hausa secondary consonants. Four children aged between 2-5 years were purposely selected. The data were collected using a Pictorial Stimulus-Driven Elicitation. The study found that reduction, simplification, and substitution phonological processes operate in some of the children’s speech production. It also revealed that regardless of the glottal stop, the second unit of the secondary consonants is more affected and that parental behavior affects children’s speech production. The implication of this result is that it can be used by speech pathology to draw a conclusion about the Hausa children’s phonological development.